2017
DOI: 10.1128/cvi.00497-16
|View full text |Cite
|
Sign up to set email alerts
|

Otitis-Prone Children Produce Functional Antibodies to Pneumolysin and Pneumococcal Polysaccharides

Abstract: The pneumococcus is a major otitis media (OM) pathogen, but data are conflicting regarding whether otitis-prone children have impaired humoral immunity to pneumococcal antigens. We and others have shown that otitis-prone and healthy children have similar antibody titers to pneumococcal proteins and polysaccharides (vaccine and nonvaccine types); however, the quality of antibodies from otitis-prone children has not been investigated. Antibody function, rather than titer, is considered to be a better correlate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Pneumolysin toxoids are an attractive vaccine candidate, because this factor is highly conserved in pneumococci (43) and tissue damage resulting from the action of the toxin is responsible for many disease symptoms (44). Additionally, immunity against pneumolysin is raised during natural infection (45), suggesting that it is available to the immune system during infection. Pneumolysin is especially relevant in protection against otitis, as it can directly cause cochlear damage and hearing loss in animal models (46), suggesting that a neutralizing antibody could protect against this sequela of AOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumolysin toxoids are an attractive vaccine candidate, because this factor is highly conserved in pneumococci (43) and tissue damage resulting from the action of the toxin is responsible for many disease symptoms (44). Additionally, immunity against pneumolysin is raised during natural infection (45), suggesting that it is available to the immune system during infection. Pneumolysin is especially relevant in protection against otitis, as it can directly cause cochlear damage and hearing loss in animal models (46), suggesting that a neutralizing antibody could protect against this sequela of AOM.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumolysin is especially relevant in protection against otitis, as it can directly cause cochlear damage and hearing loss in animal models (46), suggesting that a neutralizing antibody could protect against this sequela of AOM. Additionally, levels of antipneumolysin antibody have been correlated with reduced incidence of pneumococcal AOM in children (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although they have not studied Mcat proteins, we note that studies by the group led by Thornton and Richmond involving Australian children who experience recurrent AOM have not observed lower antibody responses to Spn proteins or capsular polysaccharides or to NTHi proteins. [38][39][40] However there are important differences in the two study populations. We study stringently-defined otitis prone (sOP) children who have every clinical diagnosis confirmed by tympanocentesis and every otopathogen identified by culture, while the Australian study population is diagnosed clinically by health care providers not directly involved in the research and in some cases middle ear fluid obtained from ruptured eardrums.…”
Section: Discussionmentioning
confidence: 99%
“…We study stringently-defined otitis prone (sOP) children who have every clinical diagnosis confirmed by tympanocentesis and every otopathogen identified by culture, while the Australian study population is diagnosed clinically by health care providers not directly involved in the research and in some cases middle ear fluid obtained from ruptured eardrums. [38][39][40] Also only 26% of our sOP children require ventilation tubes (unpublished data) while all of the Australian OP children studied for antibody responses to protein antigens were recruited at time of ventilation tube surgery. [38][39][40] Moreover, they found that Australian aboriginal (possibly similar to OP) children with otitis media displayed lower serum IgG to NTHi but not Spn proteins than non-aboriginal (possibly similar to NOP) or healthy children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation